A new species of Myrsine (Primulaceae-Myrsinoideae) from New Guinea - Utteridge, Timothy M.a.; Lepschi, Brendan J. (Phytotaxa, 2020)
Myrsine exquisitorum Utteridge & Lepschi (Primulaceae-Myrsinoideae) is described and illustrated as a new species endemic to the Western Highlands Province from Papua New Guinea. The new species is unique in the relatively large, almost orbicular leaves with entire margins, and the tetramerous flowers arranged in axillary fascicles without forming short shoots.